ANALISIS PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN KAS, DAN PERPUTARAN PERSEDIAAN TERHADAP NILAI CURRENT RATIO (Media Riset Akuntansi, 2022)
This study aims to determine the effect of working capital turnover, cash turnover, and inventory turnover on the current ratio. The sample used in this study is the PT Tiga Pilar Sejahtera Food company's financial statements for 6 years (12 semesters) starting from 2010 to 2015, so the total observations in this study are 48 observations by processing data using the Eviews 6 program. The method used in this study is multiple linear regression analysis. The results of this study indicate that working capital turnover has an effect on the current ratio, cash turnover has no effect on the current ratio and inventory turnover has an effect on the current ratio.